Family planning, work and women’s economic and social autonomy in Indonesia - Karen Hardee; Siti Hidayati Amal; Shanty Novriaty; Terence H. Hull; Elizabeth Eggleston (Asia-Pacific Population Journal, 1999)
The population programme should cater to the time constraints that women face and try to reduce their double burden caused by the inequitable division of domestic responsibilities.